The effects of PTSD treatment during pregnancy: systematic review and case study. Issue 1 (31st December 2020) - Baas, Melanie A. M.; van Pampus, Maria G.; Braam, Laura; Stramrood, Claire A. I.; de Jongh, Ad
ABSTRACT: Background: PTSD in pregnant women is associated with adverse outcomes for mothers and their children. It is unknown whether pregnant women with PTSD, or symptoms of PTSD, can receive targeted treatment that is safe and effective. Objective: The purpose of the present paper was to assess the effectiveness and safety of treatment for (symptoms of) PTSD in pregnant women. Method: A systematic review was conducted in accordance with the PRISMA guidelines in Pubmed, Embase, PsychINFO, and Cochrane. In addition, a case is presented of a pregnant woman with PTSD who received eye-movement desensitization and reprocessing (EMDR) therapy aimed at processing the memories of a previous distressing childbirth. Results: In total, 13 studies were included, involving eight types of interventions (i.e. trauma-focused cognitive behavioural therapy, exposure therapy, EMDR therapy, interpersonal psychotherapy, explorative therapy, self-hypnosis and relaxation, Survivor Moms Companion, and Seeking Safety Intervention). In three studies, the traumatic event pertained to a previous childbirth. Five studies reported obstetrical outcomes. After requesting additional information, authors of five studies indicated an absence of serious adverse events. PTSD symptoms improved in 10 studies. However, most studies carried a high risk of bias. In our case study, a pregnant woman with a PTSD diagnosis based on DSM-5 no longer fulfilled the criteria of PTSD after three sessions of EMDR therapy. She had an uncomplicated pregnancy and delivery. Conclusion: Despite the fact that case studies as the one presented here report no adverse events, and treatment is likely safe, due to the poor methodological quality of most studies it is impossible to allow inferences on the effects of any particular treatment of PTSD (symptoms) during pregnancy. Yet, given the elevated maternal stress and cortisol levels in pregnant women with PTSD, and the fact that so far no adverse effects on the unborn child have been reported associated with the application of trauma-focused therapy, treatment of PTSD during pregnancy is most likely safe.